2018
DOI: 10.1029/2018jb015490
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric Structure of Greenland From Ambient Noise and Earthquake Surface Wave Tomography

Abstract: We present a high‐resolution shear wave velocity model of Greenland's lithosphere from regional and teleseismic Rayleigh waves recorded by the Greenland Ice Sheet Monitoring Network supplemented with observations from several temporary seismic deployments. To construct Rayleigh wave group velocity maps, we integrated signals from regional and teleseismic earthquakes with several years of ambient seismic noise and used the dispersion to constrain crustal and upper‐mantle seismic shear wave velocity structure. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 117 publications
(268 reference statements)
1
39
1
Order By: Relevance
“…In this section, we review results of previous seismological studies of the crust and upper mantle structure beneath Greenland and surrounding regions, focusing mainly on seismic tomography studies. The structure has been investigated using several tomographic methods with various spatial scales, including regionalscale surface wave tomography (Antonijevic & Lees, 2018;Darbyshire et al, 2004Darbyshire et al, , 2018Levshin et al, 2017;Mordret, 2018;Pourpoint et al, 2018), surface wave tomography of the North Atlantic region (Pilidou et al, 2004), body wave tomography of the whole Arctic region (Jakovlev et al, 2012), full waveform tomography of the North Atlantic region (Rickers et al, 2013), full waveform tomography of the whole Arctic region (Lebedev et al, 2017), and global tomography (e.g., Hosseini et al, 2020;Lei et al, 2020;Zhao, 2001Zhao, , 2004Zhao et al, 2013).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we review results of previous seismological studies of the crust and upper mantle structure beneath Greenland and surrounding regions, focusing mainly on seismic tomography studies. The structure has been investigated using several tomographic methods with various spatial scales, including regionalscale surface wave tomography (Antonijevic & Lees, 2018;Darbyshire et al, 2004Darbyshire et al, , 2018Levshin et al, 2017;Mordret, 2018;Pourpoint et al, 2018), surface wave tomography of the North Atlantic region (Pilidou et al, 2004), body wave tomography of the whole Arctic region (Jakovlev et al, 2012), full waveform tomography of the North Atlantic region (Rickers et al, 2013), full waveform tomography of the whole Arctic region (Lebedev et al, 2017), and global tomography (e.g., Hosseini et al, 2020;Lei et al, 2020;Zhao, 2001Zhao, , 2004Zhao et al, 2013).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Such discrepancies are also prominent in the lower crust. Darbyshire et al (2018) and Pourpoint et al (2018) showed a nearly homogeneous velocity structure as it approaches the Moho; Levshin et al (2017) imaged almost the same velocity pattern as in the upper crust, while Mordret (2018) imaged reversed patterns in the upper and lower crust beneath southern Greenland. Lebedev et al (2017) showed only the lower crustal structure, but included low-V regions in northern Greenland and in the southern Archean block, which display similarities to the upper crustal structure of other models (Darbyshire et al, 2018;Mordret, 2018).…”
Section: Crustal Structurementioning
confidence: 99%
“…Seismic tomography and related data indicate a thick, high‐seismic‐velocity cratonic keel extending north‐south under central‐west Greenland, transected by a broad zone of lower seismic velocity approximately connecting the eastern and western Tertiary basalt provinces (Jakovlev et al, ; Lebedev et al, ; Pourpoint et al, ; Pourpoint et al, ; Rickers et al, ; Rogozhina et al, ; Figure ). The location of this low‐velocity zone is close to, or slightly north of, the majority of reconstructed tracks of the Iceland hot spot as summarized by Rogozhina et al ().…”
Section: Geologic Settingmentioning
confidence: 99%
“…We then test the plausibility of this mechanism by applying computationally efficient simulations to estimate deviatoric stress fields during glacial/interglacial cycling of the GrIS, finding widespread stresses similar to those estimated to cause dike propagation in magmatic systems. Together, these support our hypothesis that ice‐sheet processes might have contributed to anomalous GHF, and we argue that more targeted geophysical studies [e.g., Pourpoint et al ., ] informing higher‐order modeling are required to advance this work.…”
Section: Introductionmentioning
confidence: 99%